Horizontal Effect of Fundamental Freedoms and the Right to Equality after Viking and Mangold, and the Implications for Community Competence - Derrick Wyatt (Croatian Yearbook of European Law and Policy, 2008)
The judgments in Viking and Laval confirm the Court’s previous case law on the horizontal effect of Articles 39, 43 and 49 EC, and extend the horizontal effect of Articles 43 and 49 EC to cover collective action of trade unions by way of strikes, boycotts and the like. A significant knock-on effect is an extension of Community regulatory competence to cover this same subject matter, despite the contrary indications in Article 137(5) EC. The judgment in Viking implies that Article 28 EC is also capable of horizontal effect, at least in cases where collective action of individuals produces regulatory effects similar to those resulting from State action. The Court’s reasoning leaves room for future incremental increases in the horizontal effect of fundamental freedoms in cases which involve contractual rules, in particular rules regulating employed or self employed activities. The approach to horizontal effect in Viking supports, for example, the argument that provisions of a corporate constitution could amount to a restriction on freedom of establishment, as could action taken by the board of a company to frustrate a takeover bid. Advocate General Maduro in Viking argues that the Treaty rules on freedom of movement apply directly to any private action that is capable of effectively restricting others from exercising their right of freedom of movement. The present writer suggests further considerations as being relevant to determining the extent of the horizontal reach of fundamental freedoms. Normal market behaviour on the part of one market operator should not in principle be held to amount to a restriction on the fundamental freedom of another. But discriminatory conduct by market operators, or other conduct which falls outside the range of normal market behaviour, would seem capable of falling within the horizontal effect of a fundamental freedom, at any rate where it restricts access of other market operators, or consumers, to the market, or places market operators or consumers at a disadvantage because they have exercised a fundamental freedom. Account must be taken of the aims and wording of the freedom in question, along with the policy questions of whether it would be excessively burdensome to make private operators subject to the obligation to comply with the fundamental freedom in question, and whether any consequential extension of Community regulatory competence would unreasonably limit that of the Member States. A related issue to be taken into account is the possible horizontal effect of the fundamental principle of equality, as articulated in the Mangold case. Even a restrained reading of this much criticised case would suggest that the prohibition of discrimination on grounds of nationality in Article 12 EC might have horizontal effect in circumstances falling within the scope of Community law, such as the supply of goods, services, business accommodation and housing. A similar conclusion could be reached as regards discrimination in the sale of goods, services and real property to non residents. It would not be excessively burdensome to impose on private market operators the obligation not to depart from their normal terms and conditions of sale in the case of non-nationals or non-residents, unless such departure represented normal market behaviour. A possible example of discriminatory service provision contrary to the general principle of equality is that of excessive ‘roaming’ charges, which have been recently regulated by Regulation (EC) No 717/2007. A key question which arises in this context is the extent to which a market operator can, or should be able to be, justify discrimination against out of state operators, or discrimination against customers solely because they have crossed a national frontier, on grounds of normal market behaviour, when market conditions are not normal, and the market is not fully competitive.